Considering gut microbiota disturbance in the management of Helicobacter pylori infection. (2nd September 2018) - Lopetuso, Loris R.; Napoli, Marco; Rizzatti, Gianenrico; Scaldaferri, Franco; Franceschi, Francesco; Gasbarrini, Antonio
ABSTRACT: Introduction : Helicobacter pylori (Hp) infection produces drastic changes in the gastric microenvironment, which, in turn, influence the gastric microbiota composition and might be correlated with large intestinal microbiota changes. This excellent perturbing actor could trigger important modifications in the homeostatic functions exerted by gut commensals leading to a new gastrointestinal balance. At the same time, the therapeutic strategies used to eradicate Hp can modulate this physiological symbiosis, but can be also conversely affected by its properties. Area covered : The purpose of this review is to explore the reciprocal interplay between Hp infection and gut microbiota and analyze how microbial changes can influence the management of Hp eradication therapies. Expert commentary : While many studies have described Hp-dependent gut microbiota alterations, their clinical implications are only partially clear, as well as the mechanism of actions that sustain these processes. This represents a clear challenge for future research projects that will also need to understand which role is exerted by viruses, parasites, and yeasts.